Comparison of neuroendocrine responses between caudal block and local infiltration techniques in pediatric inguinal hernia surgery: A prospective comparative clinical study (Annals of Medical Research, 2026)
Aim: This study aimed to compare the effects of caudal anesthesia and local wound infiltration on postoperative stress hormone responses (cortisol and prolactin) and pain scores in pediatric patients undergoing inguinal hernia repair.Materials and Methods: A total of 64 children aged 1–4 years, classified as ASA I, scheduled for elective unilateral inguinal hernia surgery were randomized into two groups: caudal anesthesia (Group C) and local infiltration (Group I). All patients received general anesthesia. Group C received 1 mL/kg of 0.25% bupivacaine via the caudal route, while Group I received 0.25 mL/kg of 5 mg/mL bupivacaine via 23-gauge needle infiltration. Postoperative pain was assessed using the CHEOPS scale at 1st, 2nd, 3rd, and 4th hours by a blinded anesthesiologist. Blood samples for cortisol and prolactin levels were collected before induction and 40 minutes after surgery and analyzed by ECLIA.Results: No significant differences were found between groups in postoperative cortisol and prolactin levels. Pain scores were also similar at all time points (p>0.05). A significant positive correlation was observed between preoperative and postoperative prolactin levels (p
Keywords: Postoperative pain; Inguinal hernia; Wound infiltration; Caudal block; Stress hormone